Graph-Based Visual Manipulation Relationship Reasoning Network for Robotic Grasping - Zuo, Guoyu; Tong, Jiayuan; Liu, Hongxing; Chen, Wenbai; Li, Jianfeng (Frontiers in Neurorobotics, 2021)
To grasp the target object stably and orderly in the object-stacking scenes, it is important for the robot to reason the relationships between objects and obtain intelligent manipulation order for more advanced interaction between the robot and the environment. This paper proposes a novel graph-based visual manipulation relationship reasoning network (GVMRN) that directly outputs object relationships and manipulation order. Our model first extracts features and detects objects from RGB images, and then adopts Graph Convolutional Network (GCN) to collect contextual information between objects. To improve the efficiency of relation reasoning, a relationship filtering network is then built to reduce object pairs before reasoning. The experiments on the Visual Manipulation Relationship Dataset (VMRD) show that our model significantly outperforms previous methods on reasoning object relationships in object-stacking scenes. The GVMRN model is also tested on the images we collected and applied on the robot grasping platform. The results demonstrate the generalization and applicability of our method in real environment.